Use of beta-blockers and the risk of hip/femur fracture in the United Kingdom and The Netherlands. - de Vries, F; Souverein, P; Cooper, C; Leufkens, H; van Staa, T (2007)
Data from in vivo studies have indicated a role for beta-blockers in the prevention of bone loss. Some epidemiological studies have found protective effects of beta-blockers on fracture risk. However, there is limited information on the association with cumulative dose and type of beta-blockers used. We conducted two case-control studies using data from the UK General Practice Research Database (GPRD) and the Dutch PHARMO Record Linkage System (RLS). Cases were patients with a first hip or femur fracture; controls were individually matched on practice/region, gender, year of birth, and calendar time. Current use of beta-blockers was defined as a prescription in 90 days before the index date. We adjusted for medical conditions and drugs associated with falling or bone mineral density. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using conditional logistic regression analysis. The study population included 22,247 cases and controls in the GPRD and 6,763 cases and 26,341 controls in the PHARMO RLS. Current use of beta-blockers was associated with a reduced risk of hip/femur fracture in both the GPRD (adjusted OR = 0.82, 95% CI 0.74-0.91) and PHARMO RLS (adjusted OR = 0.87, 95% CI 0.80-0.95) study populations. However, this reduction of risk was not associated with cumulative dose, lipophilicity, or receptor selectivity of beta-blockers. The protective effect of beta-blockers was only present among patients with a history of use of other antihypertensive agents (GPRD adjusted OR = 0.72, 95% CI 0.64-0.83; PHARMO RLS adjusted OR = 0.76, 95% CI 0.67-0.86) but not in patients using beta-blockers only (GPRD adjusted OR = 0.97, 95% CI 0.82-1.14; PHARMO RLS adjusted OR = 1.01, 95% CI 0.90-1.14). Also, in patients with a history of use of other antihypertensive agents, no dose-response relationship with beta-blocker use was found. The effect was constant with cumulative dose and the OR was below 1.0 even among patients who just started treatment with beta-blockers. As the mechanism by which beta-blockers could influence bone mineral density is likely to need some time to exert a clinically relevant effect, all these finding suggests that the association between beta-blockers and fracture risk is not causal.